THE EUROPEAN UNION DIRECTIVE PROPOSAL ON RESTRUCTURING AND SECOND CHANCE: A CHECK OF COMPLIANCE BY ROMANIAN LAW - Corina Georgiana COSTEA (Challenges of the Knowledge Society, 2018)
The European Commission is highly active in the field of insolvency, by making big steps towards reforming the concept of insolvency, beginning with the Recast of the European Insolvency Regulation, which has entered into force on 26th of June 2017, with small exceptions. On 22nd November 2016, the European Commission presented the Proposal for a Directive on restructuring frameworks, second chance and measures to increase the efficiency of restructuring, insolvency and discharge procedures and amending Directive 2012/30/UE. The Proposal itself aims at reforming the concept of insolvency by trying to build a new entrepreneurial culture, based on rescuing financially distressed yet viable debtors. The effects of the actual European culture regarding insolvency, which prioritizes liquidation, have been quantified in job losses, a high rate of nonperforming loans and low percentage of creditors’ recovery rate. The Proposal invites Member States to put in place its provisions, by offering them a set of key principles and rules. The Proposal's general objective is to eliminate the barriers to the free flow of capital, but it also provides adjacent targets, which encourage cross-border investments and limit the rate of non-performing loans. This paper aims to analyze a check of compliance by Romanian law, in order to identify the way that our national law will need to be adapted to the Proposal's provisions.